Towards a virtual statecraft: Housing targets and the governance of urban housing markets. (December 2022) - Raco, Mike; Ward, Callum; Brill, Frances; Sanderson, Danielle; Freire-Trigo, Sonia; Ferm, Jess; Hamiduddin, Iqbal; Livingstone, Nicola
Abstract: In this paper we draw on the findings of a mixed methods research project that has examined the production, regulation, and delivery of housing in London. Our aim is to develop fresh insights into the growing mobilisation of numbers and targets in contemporary planning systems. More specifically, we bring two fields of literature into conversation. First, drawing on recent contributions from Pike et al. (2019) we develop their notion of 'city statecraft or the art of city government and management of state affairs and relations (p.79). We discuss how and why their framing of contemporary urban governance captures current trends in contemporary cities, including: the financialisation of housing and infrastructure; the rolling-out of delivery-focused public private partnerships; and the broader political projects that underpin planning priorities. The paper combines these insights with wider writings in urban studies on virtualism or the analysis of theories and governmental practices that seek to make the world conform to pre-existing ideas, rather than describing and explaining its formation. We argue that target-based forms of governance represent the implementation of a virtual statecraft in which the material realities of actual places become simulated worlds, ripe for calculation and re-making. We show, through in-depth research on housing regulation and investment/development trends in London, the ways in which virtual forms of statecraft are developed and implemented and with what effects on the material outcomes of urban development processes. The findings are of comparative significance as planning systems across Europe and beyond are becoming increasingly focused on market-oriented oriented forms of planning in an effort to boost the production of housing and to deliver social policy outcomes.